Comparative Microbiome Signatures and Short-Chain Fatty Acids in Mouse, Rat, Non-human Primate, and Human Feces - Nagpal, Ravinder; Wang, Shaohua; Solberg Woods, Leah C.; Seshie, Osborne; Chung, Stephanie T.; Shively, Carol A.; Register, Thomas C.; Craft, Suzanne; McClain, Donald A.; Yadav, Hariom (Frontiers in Microbiology, 2018)
Gut microbiome plays a fundamental role in several aspects of host health and diseases. There has been an exponential surge in the use of animal models that can mimic different phenotypes of the human intestinal ecosystem. However, data on host species-specific signatures of gut microbiome and its metabolites like short-chain fatty acids (SCFAs; i.e., acetate, propionate, and butyrate) and lactate in these models and their similarities/ differences from humans remain limited, due to high variability in protocols and analyses. Here, we analyze the fecal microbiota composition and the fecal levels of SCFAs and lactate in three of the most-widely used animal models i.e., mice, rats and non-human primates (NHPs) and compare them with human subjects, using data generated on a single platform with same protocols. The data show several species-specific similarities and differences in the gut microbiota and fecal organic acids between these species groups. Based on β-diversity, the gut microbiota in humans seems to be closer to NHPs than to mice and rats; however, among rodents, mice microbiota appears to be closer to humans than rats. The phylum-level analyses demonstrate higher Firmicutes-Bacteroidetes ratio in humans and NHPs vs. mice and rats. Human microbiota is dominated by Bacteroides followed by Ruminococcaceae and Clostridiales. Mouse gut is predominated by members of the family S24-7 followed by those from the order Clostridiales, whereas rats and NHPs have higher abundance of Prevotella compared with mice and humans. Also, fecal levels of lactate are higher in mice and rats vs. NHPs and humans, while acetate is highest in human feces. These data of host species-specific gut microbiota signatures in some of the most widely used animal models in context to the human microbiota might reflect disparities in host factors e.g., diets, genetic origin, gender and age, and hence call for prospective studies investigating the features of gut microbiome in such animal models by controlling for these host elements.